HIV AND HERPETIC INFECTIONS: MODERN IMMUNOLOGICAL LABORATORY ASPECTS - Gubaydulina Gulmira Rifkatovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: Human immunodeficiency virus (HIV) infection is frequently accompanied by opportunistic and co-infections, among which herpetic infections occupy a leading position. Herpes simplex virus (HSV-1, HSV-2), cytomegalovirus (CMV), Epstein–Barr virus (EBV), and varicella-zoster virus (VZV) significantly influence the clinical course of HIV infection, immune status, and disease progression. This article reviews the clinical manifestations of herpetic infections in HIV-positive patients and highlights key immunological and laboratory features that are essential for diagnosis, monitoring, and therapeutic decision-making.